Exfoliation level of aggregated graphitic nanoplatelets by oxidation followed by silanization on controlling mechanical and nanomechanical performance of hybrid CFRP composites. (15th September 2019) - Khan, Nazrul Islam; Halder, Sudipta; Das, Subhankar; Wang, Jialai
Abstract: Effective functionalization of graphitic nano-fillers for better exfoliation and interfacial interaction with epoxy matrix is highly desirable for fabrication of high-performance laminated composites. This paper demonstrates the level of exfoliation of low cost aggregated graphitic nanoplatelets (GNPs) through a facile oxidation method and their amine functionalization to use as reinforcement in hybrid carbon fiber reinforced polymer (CFRP) composite with improved interfacial properties. The morphologies, surface functional groups, surface topography, surface elements, structural information of amine functionalized GNPs were characterized by FESEM, FT-IR, AFM, XPS, Raman analysis respectively. The hybrid CFRPs reinforced with 60 h of oxidized followed by silanized GNPs (OSG-60) demonstrated significant improvement in tensile strength (∼97%), flexural strength (∼62.3%) and interlaminar shear strength (∼27.42%) with respect to the control. Topographic investigation of OSG-60 demonstrates exfoliation of graphene sheets up to ∼2 to 3 layers along with uniformly decorated amine based silane moieties after silanization. Assessing the interfacial nanomechanical properties of hybrid CFRP having OSG-60 through nanoindentation, we found ∼33.41% enhancement in interfacial stiffness at the juncture of the fibers within the inter-ply region. Thus, this work provides a clear insight of an industrial ready method for delivering a durable and high-performance hybrid CFRP composites. Graphical abstract: Image 1